Frequency and number of resuscitation related rib and sternum fractures are higher than generally considered. (August 2015) - Kralj, Eduard; Podbregar, Matej; Kejžar, Nataša; Balažic, Jože
Abstract: Aim of the study: This study aimed to establish the incidence, number and location of CPR-related skeletal chest injuries (SCI) and to investigate the influence of age, gender, changes in resuscitation guidelines and technique of resuscitation. Methods: We analysed SCI in 2148 patients who had undergone resuscitation for non-traumatic cardiac arrest, as shown by autopsies performed at the Institute of Forensic Medicine in Ljubljana in the period 2004–2013. Results: External cardiac massage caused SCI in 86% of males and in 91% of females; sternum fractures occurred in 59% of males and 79% of females, rib fractures in 77% of males and 85% of females and sternocostal separations in 33% of males and 12% of females. The average number of all SCI per person was thus almost the same in males and females: 10.95 vs. 10.96. The percentage of patients injured and the number of SCI increased with age. Changes in resuscitation guidelines were also identified as a factor contributing to the incidence and number of SCI. No adverse effect of the use of LUCAS was found. Conclusion: It is generally considered that at least 1/3 of resuscitated patients sustain rib fractures and at least 1/5 sustains sternum fractures. However, our study showed that these injuries are much more frequent and that increased compression rate and depth cause more SCI. Since in the period 2011–2013 accompanying severe injuries occurred in only 1.85% of cases, the resuscitation technique has not yet jeopardised patient's safety, but further close monitoring is needed.